Promises and challenges of deliberative and participatory innovations in hybride regimes: The case of two citizens’ assemblies in Serbia - Fiket Irena; Đorđević Biljana (Filozofija i Društvo, 2022)
A worrying trend of autocratization that has been spreading globally in recent years, has thrust forward a new wave of appeals for deliberative and participatory democracy as a remedy for the crisis. With a few exceptions, the majority of participatory and deliberative institutions were implemented in stable democracies. The efforts to institutionalize participatory and deliberative models are almost completely absent in Serbia and other Western Balkan countries. Yet, there has been a trend of citizen mobilization in the form of social movements and local civic initiatives, which are both a symptom of unresponsive and quite openly authoritarian institutions, as well as a potential pathway to democratization. The pace and scope of these developments in the undemocratic societies of the Western Balkan region, in terms of both bottom up and top-down democratic experimentation, call for a better understanding of their internal dynamics, and their social and political impact. Responding to this need, the articles in the special issue focus on social movement mobilizations and deliberative experimentation. To begin with, our introductory article focuses particularly on understanding the possible role deliberative institutions could have in hybrid regimes. It looks at the first two cases of deliberative mini publics (DMPs) ever organized in Serbia, analyzing their rationale, specific design, implementation, as well as considering the possible role deliberative institutions could play in the hybrid regime of Serbia.